Implementation of Ulin Ethno-Wellness Treatment to Enhance Sleep Quality Among Students of Bachelor in Beauty and Hair Management, MSU Malaysia - Christine Ulina Tarigan; Warda Indadihayati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
International community service program activities, carried out with Ulin Ethno-Wellness Treatment training to improve sleep quality, for students in Management and Science University’s Bachelor's in Beauty and Hair Management, have provided significant benefits. The main goal is to improve the knowledge and skills of students to be able to understand Spa techniques with the use of traditional spices. The implementation of these activities was carried out through material and demonstration activities on the application of Ethno-Wellness Treatment. The implementation of this activity is considered successful, with the fulfillment of the participant quota, the implementation scheduled as planned, and the benefits provided to the participants.